A comparison study of rail fault detection methods in the literature - Taştimur, Canan; Karaköse, Mehmet; Akın, Erhan (My University, 2017)
Railsareone of themostimportantcomponents of railwaytransportation. It is neededthattherails can be observed at regularinterval in ordertoensurethesafety of railwaytransportation, preventthedisruption of transportation, andavoidaccidents. To be inspected of railsurfacebyusingmanualtechniques, bothdamagestherailsurfaceandleadstodisruption of railway transport. Railprofileanalysismethodsthatutilizecontactlessimageprocessi ngtechniquesareavailable in theliterature in ordertoavoidtheseproblems. Thispaperpresents a comparison of raildefectdetectionmethodsthatareavailable in theliterature. Thesemethods in theliteraturehavebeencompared in terms of feasibility, performance, accuracy, elapsed time, andimageprocessingtechniquesused. Theadvantagesanddisadvantages of thesemethodsrelativetoeachotherareexamined in thisarticle
Bildiri - Yayımlanmış
Keywords: Rail defects; image processing techniques; Defect detection; Rail surface analysis